(untitled) (Indian Journal of Arid Horticulture, 2025)
Bael (Aegle marmelos Correa) is one of the impor- tant minor fruit crop with high nutritive and medicinal value. It is mainly propagated either by seed or "T" budding or soft wood grafting. True to type plants can be produced in latter two methods but the growth is very slow. Tissue culture technique offers an advantage over conventional methods of propagations in producing large number of true to type plants from healthy elite plant within a short period of time. The surface sterilization is the most impor- tant step in micro-propagation and become a critical step in establishment of certain species particularly when the explants are derived from field grown plants. In this per- spective studies were undertaken to standardize the pro- tocol for surface sterilization of nodal segment of field grown plant of bael.